A THEORETICAL FRAMEWORK FOR WORKPLACE SPIRITUALITY, JOB SATISFACTION, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Ravina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Researchers and practitioners in management have noted a growing and sustained interest in issues related to spirituality in the workplace. This article reflects on the existing literature of workplace spirituality, highlights emerging theories, and explores the connections between job satisfaction and organizational citizenship behaviours (OCBs). Workplace spirituality has garnered growing attention in recent years. This article explores the interactions between the three variables, namely workplace spirituality, job satisfaction, and OCBs, and further examines the links of several kinds of OCBs with the three major aspects of workplace spirituality (that is, seeking meaning and purpose in work, acknowledging an inner life, and feeling connected to others). It was found that Job satisfaction plays a key role in this relationship. The study aims to offer valuable insights for improving management practices, leadership, and organizational growth by creating an environment that encourages workplace spirituality.